Factors implementation of facility management (FM) in Malaysia construction - Ahmed Sai’d Sa’deh, Abdullah (2018)
Facilities management (FM) previously was known as the poor connection within the land, architecture, engineering and construction engineers because it was in the old-fashioned sense of cleaning maintenance and repairs. It’s obvious that (FM) covers a lot of terms in wide range of functions and properties. To conduct the study, the ultimate objective of the study should be specified so that the study can be done thoroughly according to its aim. Several objectives should be specified to support the ultimate objectives so that the finding could be justified. The aim of this study is to determine the causes of the problems occurred in facilities management. In order to achieve this aim, several objectives have been set which are: study the current situation of FM in Kuala Lumpur and Pahang and identify the barriers factors on implementing facility management then Analyze and identify the most barriers. The discussion on implementing facility management is conducted in Malaysia which the factors are prepared depending on the fields industry in Malaysia such as; organization, cost, technology, roles and responsibility and maintenance and operation. All these factors have each one five sub-factors to use in the questionnaire paper to survey it to contractors, consultants, owners and industrial companies. Then, by using Relative Importance Indices (RII) method, the collected data were analyzed.